Toxoplasma-Induced Hypermigration of Primary Cortical Microglia Implicates GABAergic Signaling - Bhandage, Amol K.; Kanatani, Sachie; Barragan, Antonio (Frontiers in Cellular and Infection Microbiology, 2019)
Toxoplasma gondii is a widespread obligate intracellular parasite that causes chronic infection and life-threatening acute infection in the central nervous system. Previous work identified Toxoplasma-infected microglia and astrocytes during reactivated infections in mice, indicating an implication of glial cells in acute toxoplasmic encephalitis. However, the mechanisms leading to the spread of Toxoplasma in the brain parenchyma remain unknown. Here, we report that, shortly after invasion by T. gondii tachyzoites, parasitized microglia, but not parasitized astrocytes, undergo rapid morphological changes and exhibit dramatically enhanced migration in 2-dimensional and 3-dimensional matrix confinements. Interestingly, primary microglia secreted the neurotransmitter γ-aminobutyric acid (GABA) in the supernatant as a consequence of T. gondii infection but not upon stimulation with LPS or heat-inactivated T. gondii. Further, microglia transcriptionally expressed components of the GABAergic machinery, including GABA-A receptor subunits, regulatory molecules and voltage-dependent calcium channels (VDCCs). Further, their transcriptional expression was modulated by challenge with T. gondii. Transcriptional analysis indicated that GABA was synthesized via both, the conventional pathway (glutamate decarboxylases GAD65 and GAD67) and a more recently characterized alternative pathway (aldehyde dehydrogenases ALDH2 and ALDH1a1). Pharmacological inhibitors targeting GABA synthesis, GABA-A receptors, GABA-A regulators and VDCC signaling inhibited Toxoplasma-induced hypermotility of microglia. Altogether, we show that primary microglia express a GABAergic machinery and that T. gondii induces hypermigration of microglia in a GABA-dependent fashion. We hypothesize that migratory activation of parasitized microglia by Toxoplasma may promote parasite dissemination in the brain parenchyma.